Total Graph Interpretation of the Numbers of the Fibonacci Type - Urszula Bednarz; Iwona Włoch; Małgorzata Wołowiec-Musiał (Journal of Applied Mathematics)
We give a total graph interpretation of the numbers of the Fibonacci type. This graph interpretation relates to an edge colouring by monochromatic paths in graphs. We will show that it works for almost all numbers of the Fibonacci type. Moreover, we give the lower bound and the upper bound for the number of all (A1,2A1)-edge colourings in trees.